Tricyclic Antidepressants in Nociceptive and Neuropathic Pain: A Review of Their Analgesic Properties in Combination With Opioids. (February 2023) - Reinert, Justin P.; Veronin, Michael A.; Medina, Christopher
Objectives: To determine the efficacy and safety of commonly prescribed tricyclic antidepressants (TCAs) as analgesics for nociceptive and neuropathic pain in combination with opioids.Data Sources: A comprehensive literature review was conducted with the assistance of a medical reference librarian on PubMed, MEDLINE, Scopus, and Web of Science using the following search terminology: "Amitriptyline" OR "Doxepin" OR "Desipramine" OR "Imipramine" OR "Nortriptyline" OR "Clomipramine" OR "Trimipramine" AND "Analgesia." Reports of adult patients who received any TCA as an adjunctive analgesic to opioids were included.Study Selection and Data Extraction: A total of 293 results were obtained from the initial database inquiries, following which exclusion criteria were applied and 6 articles were included in this review. Three of the reports detailed the use of TCAs in the perioperative setting, whereas the remaining 3 evaluated their effect on different etiologies of neuropathic pain.Data Synthesis: Tricyclic antidepressants were found to have modest, yet not insignificant, independent analgesic properties, although the ability to provide pain relief was relegated to a select few agents. Desipramine has the most data available for use in nociceptive, postoperative pain through its ability to potentiate and prolong the analgesic effects of opioids and was not associated with adverse drug effects.Conclusions: The efficacy of TCAs for neuropathic pain was not corroborated by this review, and the anticholinergic adverse effects associated with this drug class were found to be significant. Further research is needed to quantify the efficacy of TCAs in the management of nociceptive pain.